THE CRITICAL SUCCESS FACTORS THAT INFLUENCE ORGANISATIONS TO ADOPT INTERNET TECHNOLOGY - Tam, Lloyed Yew King (Malaysian Journal of Library and Information Science, 2001)
This paper highlights the salient factors used by IT organisations to adopt Internet technology at different adoption period. Five organisational and two marketplace factors were used in this study. The final analysis confirmed that earlier adopters were influenced more by the five organisational factors: perceived direct benefits, organisational compatibility, trading partner pressure, organisational support, and perceived in-direct benefits. Both early and late adopters were not influenced by the technical complexity construct. Another factor, competitive pressure was not internally consistent.